Awareness of Antimicrobial Resistance in the Community: The Role of the WHO in Addressing Consumer Information Needs. Issue 4 (1st October 2020) - Rajkhowa, Arjun; Thursky, Karin
Abstract: The global rise of drug-resistant infections is an urgent concern but public engagement on the issue tends to be sporadic. Antimicrobial resistance (AMR) is contributing to increased morbidity and mortality from infections globally. Effective mitigation of AMR has been recognized by governments and non-governmental bodies internationally as a priority, though mitigation efforts have not received widespread attention. The World Health Organization (WHO) has played a key role in drawing governments' attention to the phenomenon and in coordinating inter-governmental mitigation efforts. It has also played a key role in raising community awareness of AMR. This article explores the WHO's role in analyzing community information needs regarding appropriate antimicrobial use, and provides an overview of its online information resources to help drive public awareness of AMR and the need for appropriate antimicrobial use. It reviews research commissioned by the WHO on public knowledge of AMR and antimicrobial use, and on the uptake of public awareness campaigns, as well as online consumer-directed posters and info-graphics developed by the WHO for its flagship public awareness campaign, Antibiotic Awareness Week.